Реформування та розвиток фізичного виховання - Подольський, Денис Русланович (Тернопіль, ЗУНУ, 2025)
У роботі досліджено теоретико-методологічні основи реформування фізичного виховання. Проведено оцінку інноваційних напрямів розвитку фізичного виховання в Україні. Опрацьовано зарубіжні моделі організації фізичного виховання, виконано їх порівняльний аналіз. Обґрунтовано концепцію реформування системи фізичного виховання в Україні. Розроблено модель інноваційної системи фізичного виховання. The work examines the theoretical and methodological foundations of physical education reform. An assessment of innovative directions in the development of physical education in Ukraine has been carried out. Foreign models of physical education organization have been studied and a comparative analysis has been performed. The concept of reforming the physical education system in Ukraine has been substantiated. A model of an innovative physical education system has been developed.
Reforming and developing of physical education